Psychodynamic insights from narratives of people with amyotrophic lateral sclerosis: A qualitative phenomenological study - Andrea Caputo (Mediterranean Journal of Clinical Psychology, 2019)
This study explored the illness experience of people with amyotrophic lateral sclerosis (ALS) to widen narrative research on patients’ perspectives, adopting object relations theory as interpretative framework. A qualitative phenomenological analysis was conducted on the illness stories of 12 adult Italian patients with ALS, collected through an Internet-based database for the sharing of illness experiences of people with rare and chronic degenerative diseases. Three thematic areas were identified: “the experience of ALS from symptom onset to diagnosis”, “impact of illness”, and “coping with illness”. Overall, the central conflict experienced by people with ALS refers to the progressive loss of control on bodily experience, that is handled by means of denial and splitting defences to contrast such a process of somatic depersonalization. As well, the investment on interpersonal domain responds to a repairing strategy ensuring psychic vitality and sensorial integration to rebuild the relation between the self and the external world.